PENGARUH PENDEKATAN SAINTIFIK BERBASIS OUTDOOR STUDY TERHADAP KEMAMPUAN BERPIKIR SPASIAL PESERTA DIDIK - Agustinus Hale Manek; Bella Theo Tomi Pamungkas; Andrinata Andrinata; Sunimbar Sunimbar; Mikael Samin (Jurnal Geografi, 2025)
The scientific approach based on Outdoor Study provides an innovative alternative in geography learning by utilizing the environment as a direct learning resource. This study aims to determine the effect of the scientific approach based on Outdoor Study on students' spatial thinking skills. The research design used a quasi-experimental method with a pretest-posttest nonequivalent control group design. The subjects of the study were students of grade XI S.1 and XI S.2 at SMA Negeri 2 Kupang City. The instrument used was a spatial thinking ability test validated by experts. Data analysis used an independent sample t-test through SPSS 16.00 for Windows. The test results showed a Sig. (2-tailed) value of 0.000 which is smaller than 0.05, so it is concluded that there is a significant effect of the scientific approach based on Outdoor Study on students' spatial thinking skills. These findings indicate that geography learning through direct interaction with the surrounding environment can improve spatial thinking skills significantly.